UNDERSTANDING AND REFLECTION OF ISSUES IN LANGUAGE EDUCATION RESEARCH - Iwan Jazadi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
As future researchers, can students and practitioners in language education just enter an actual research project without adequate theoretical understanding of it. Can they expect that they would understand it while doing the research. If not, what sorts of understanding should they possess. In other words, are there several issues which should be addressed in order that they are well informed about how and what to carry out research satisfactorily. The answer to this last question is „yes‟, even not only addressed to students, but also to school teachers and lecturers or the academic community at large. This is because theoretical understanding should continue to be developed berita terkini update and refreshed. Consequently, before embarking on a research project, one should understand some key updated issues which develop around her/his field of specialization, both global and local issues. Global issues involve the development of new or popular trends in social sciences and particularly in language educational research. In addition the intertextual relations of research in the field and other related fields, the interconnection between and among researchers and other stakeholders should be taken into consideration. The local issues include the possibilities of carrying out research in a certain context which may differ depending on the contexts, the means available as well as the constraints which influence the research implementation. All these informing issues are of high contribution for making decisions about doing research. The discussion is compelling because, as a matter of fact, literature in English language teaching (e.g., articles in TEFLIN Journal, „Indonesian Linguistic Journal‟, and many open access national and international journals) has not given a comprehensive attention on how stakeholders in research should manage each of their power, how ethical issues should be dealt with properly, and how trustworthiness is particularly addressed. Generally informed by social sciences research literature and relevant ELT references, the author highlights the major decisions which researchers are faced with, in relation to power, ethics, truth claims and methodological considerations in research. Based on the highlights, the author then reflects on the issues for carrying out research in Indonesian English language teaching contexts as informed by his professional experience and observation